STUDIES ON THE JUVENILE FISH STOCK OF CHILKA LAKE - Kowtal, G V (Indian Journal of Fisheries, 2011)
The fishery of Chilka Lake is dependent on successful recruitment of juveniles from the adjoining Bay of Bengal. It has been estimated that these recruits contribute to nearly 70 to 80% of the fishery, which is composed of mainly prawns, mullets and perches, which grow in the lake to larger sizes. These juveniles can be collected and utilised profitably for brackishwater fish-culture industry.